Student’s Verbal Mathematical Communication Skills when Presenting Vector Material - Rohmawati, Sinta; In'am, Akhsanul; Zukhrufurrohmah (UNNES JOURNAL, 2024)
Students must master oral mathematical communication because it is often used to convey ideas during discussions or presentations. This research aims to describe students' verbal and mathematical communication skills on vector material. This research uses a qualitative approach with a descriptive research type. The subjects in this research were second-year students of the Mathematics Education study program. The instruments used were verbal and mathematical communication ability test sheets, and the data was validated through video recordings of student explanations and drafts collected by students. Data analysis techniques are carried out by presenting, condensing, and drawing conclusions. This research shows that students have good oral mathematical communication skills of 45%, meaning they can convey their ideas orally well. Most indicators are fulfilled in aspect (1) indicator (b), namely accuracy in conveying or demonstrating the use of concepts in problem examples. Good mathematical communication skills have a good and structured thought process so students can share ideas orally well. Mahasiswa perlu menguasi komunikasi matematis lisan karena sering digunakan dalam menyampaikan gagasan saat diskusi atupun presentasi. Penelitian ini bertujuan mendeskripsikan kemampuan komunikasi matematis lisan mahasiswa pada materi vektor. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Subjek pada penelitian ini mahasiswa tahun kedua prodi Pendidikan Matematika. Instrumen yang digunakan yaitu lembar tes kemampuan komunikasi matematis lisan dan data divalidasi melalui video rekaman penjelasan mahasiswa dan draf yang dikumpulkan mahasiswa. Teknik analisis data dilakukan dengan cara penyajian data, kondensasi data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa mahasiswa memiliki kemampuan komunikasi matematis lisan berkategori baik sebanyak 45%, artinya mahasiswa dapat menyampaikan ide pemikirannya secara lisan dengan baik. Indikator paling banyak terpenuhi pada aspek (1) indikator (b) yaitu ketepatan menyampaikan atau mendemonstrasikan penggunaan konsep pada contoh permasalahan. Kemampuan komunikasi matematis yang baik memiliki proses berpikir yang baik dan terstruktur sehingga mahasiswa bisa menyampaikan ide secara lisan dengan baik.